Aleukaemic leukaemia presenting with pathological fracture - Chua, Gilbert T (BMJ Publishing Group, 2014)
A 19-month-old Chinese girl presented with pathological fracture of her right distal tibia. Peripheral blood revealed no abnormal cells, electrolytes were normal and bone biopsy at the fracture site only showed small aggregates of unremarkable lymphocytes. A bone marrow study could not provide a definitive diagnosis of acute leukaemia on morphology and immunohistochemistry. A diagnosis of precursor B-cell acute lymphoblastic leukaemia was unequivocally confirmed by a cytogenetic study which showed a hyperdiploid clone with gain of chromosome 4 among other trisomies.